Comparative transcriptome analysis in two contrasting genotypes for Sclerotinia sclerotiorum resistance in sunflower. - Mingzhu Zhao; Bing Yi; Xiaohong Liu; Dexing Wang; Dianxiu Song; Enyu Sun; Liangji Cui; Jingang Liu; Liangshan Feng (PLoS ONE)
Sclerotinia sclerotiorum as a necrotrophic fungus causes the devastating diseases in many important oilseed crops worldwide. The preferred strategy for controlling S. sclerotiorum is to develop resistant varieties, but the molecular mechanisms underlying S. sclerotiorum resistance remain poorly defined in sunflower (Helianthus annuus). Here, a comparative transcriptomic analysis was performed in leaves of two contrasting sunflower genotypes, disease susceptible (DS) B728 and disease resistant (DR) C6 after S. sclerotiorum inoculation. At 24 h post-inoculation, the DR genotype exhibited no visible growth of the hyphae as well as greater activity of superoxide dismutase activity (SOD), peroxidase (POD), catalase (CAT), glutathione-S-transferase (GST), ascorbate peroxidase (APX) and monodehydroascorbate reductase (MDAR) than DS genotype. A total of 10151 and 7439 differentially expressed genes (DEGs) were detected in DS and DR genotypes, respectively. Most of DEGs were enriched in cell wall organisation, protein kinase activity, hormone, transcription factor activities, redox homeostasis, immune response, and secondary metabolism. Differential expression of genes involved in expansins, pectate lyase activities, ethylene biosynthesis and signaling and antioxidant activity after S. sclerotiorum infection could potentially be responsible for the differential resistance among two genotypes. In summary, these finding provide additional insights into the potential molecular mechanisms of S. sclerotiorum's defense response and facilitate the breeding of Sclerotinia-resistant sunflower varieties.